UJI EKSPERIMENTAL EFISIENSI TERMAL SERPENTINE SOLAR WATER HEATER DENGAN LAJU ALIRAN AIR 1 LPM - Yustisia Ahnaf; Nugroho Agung Pambudi; Husin Bugis (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
Solar water heater is a device that uses solar collectors to absorb solar radiation and convert it into heat energy to heat water. The type of solar collector and the water flow rate used affect the thermal efficiency of the solar water heater. This research uses a solar water heater with a serpentine configuration of copper pipe material and applies a water flow rate of 1 lpm. The purpose of this research is to determine the effect of water flow rate on the thermal efficiency produced by solar water heater with serpentine configuration. The type of research is quantitative research, with experimental methods. This research was conducted at Campus V, Sebelas Maret University Surakarta for 3 days starting at 09.00 to 15.00 WIB. The test results of the serpentine solar water heater with a water flow rate of 1 lpm produced the highest temperature reaching 43.42 ͦC and had a thermal efficiency of 46.14%.